Traditional Chinese Medicine and Medical Liability: Regulatory and Judicial Developments and Future Prospects (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The growing popularity of Traditional Chinese Medicine (TCM) in Italy raises important medical-legal and ethical issues. Although increasingly present in hospitals, universities and in the management of chronic diseases, TCM is not recognised as an autonomous discipline: it is classified as an unconventional practice reserved for doctors. The absence of specific legislation creates uncertainty regarding informed consent, standards of care and professional responsibility. The article also analyses recent case law and ethical principles, highlighting the need for a clearer regulatory framework, accurate documentation, interdisciplinary communication and continuous training to ensure safety and professional protection.